Juridical Study of Early Marriage (Case Study on Lombok Island) - Zaenul Haq (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
Early marriage has recently become a very interesting topic to discuss, both from the perspective of Indonesian national law and Islamic law, as well as from the standpoint of psychological impact research. Early marriage has actually been happening for a long time, but it remains a very interesting issue to study. In this research, the researcher will discuss early marriage from the perspective of Indonesian national law and compare it with Islamic law, as well as the psychological impacts of early marriage, particularly those occurring on the island of Lombok. By discussing it from the perspective of Indonesian positive law and comparing it with Islamic law as well as the psychological impacts, the researcher hopes that this study will become a beneficial piece of writing to enrich the wealth of knowledge, especially in the field of legal studies. The research method used in this study employs the normative juridical research method. The normative juridical research method is a legal research method that examines the internal aspects of positive law by studying library materials or secondary data.This approach is also known as the library approach.